Associations between perceived stress and BMI and waist circumference in Chinese adults: data from the 2015 China Health and Nutrition Survey. Issue 15 (14th October 2021) - Tan, Tian; Leung, Cindy W
Abstract: Objectives: To assess the association between perceived stress and adiposity among Chinese adults. Design: Cross-sectional study. Perceived stress was assessed using the 14-item perceived stress scale. Associations between quintiles of perceived stress and BMI and waist circumference were assessed using linear regression models and multinomial regression models. Estimates were adjusted for sociodemographic characteristics. Setting: 2015 China Health and Nutrition Survey: 12 provinces covering a variety of geographic, economic development and health indicator situations. Participants: A total of 8385 adults of both sexes, aged 18–99 years, were included. Results: Overall, the mean perceived stress score was 22·7 (6·2), mean BMI was 24·3 (3·6) kg/m 2 and prevalence of obesity (BMI ≥ 30 kg/m 2 ) was 6·0 %. There were inverse associations between perceived stress quintiles with continuous BMI ( P < 0·001), BMI categories ( P = 0·015) and waist circumference ( P = 0·047). Compared to adults in the lowest quintile of perceived stress, adults in the highest quintile of perceived stress had 0·44 kg/m 2 lower mean BMI (95 % CI: −0·67, −0·21), 0·72 times the prevalence of obesity (95 % CI: 0·55, 0·94) and 0·73 times the prevalence of abdominal obesity (95 % CI: 0·61, 0·88). Results were similar when using Chinese-specific cut-points. Conclusion: Our results showed inverse associations between perceived stress quintiles and adiposity among Chinese adults. Future studies should aim to better understand the directionality of the observed associations and the potential biological and behavioural mechanisms underlying these associations in the Chinese population.